Pemetaan Bibliometrik dengan VOSviewer terhadap Pengetahuan Lokal Mitigasi Bencana - Yusuf, Alifa Ufaira; Erwina, Wina; Winoto, Yunus (UPT Perpustakaan UIN Alauddin Makassar, 2024)
Bibliometric mapping can describe variations in information regarding local knowledge in an effort to reduce the impact of disasters. Although there has been much discussion about bibliometric mapping, research on local knowledge in the context of disaster mitigation is still very limited. Research methods. The bibliometric method with a quantitative approach is applied through the Scopus database with a range of 2019-2023 and VOSviewer visualization. The mapping technique is carried out using co-citation analysis and network and density visualization. Analysis data. There were 98 documents that cited two studies simultaneously. The most cited research discusses local knowledge for disaster preparedness and the integration of indigenous knowledge with science for disaster risk reduction. Results and Discussion. The research relationship pattern resulted in 8 clusters with different topic focuses, ranging from the integration of indigenous knowledge and scientific knowledge in disaster resilience, disaster risk management, to community participation.